2023
DOI: 10.1021/acsnano.3c00026
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Remote Epitaxial Heterointerface by Graphene-Assisted Attenuative Charge Transfer

Abstract: Remote epitaxy (RE), substrate polarity can "penetrate" two-dimensional materials (2DMs) and act on the epi-layer, showing a prospective universal growth strategy. However, essentially, the role that 2DMs plays in RE has not been deeply investigated so far. Here, the RE of single-crystal films on the weakest polarity/iconicity substrate is realized to reveal its essence physical properties. Graphene facilitates attenuative charge transfer (ACT) from a substrate to epi-layer to construct remote interactions. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…Numerous pinholes were present in STO film (RMS = 1.10 nm), which was in direct contact with Si, whereas a very smooth layer with atomic-scale surface roughness (RMS = 0.34 nm) was observed for STO overgrown on rGO-buffered Si. The lower diffusion energy barrier of rGO compared to that of SiO 2 enables the depositing materials to more easily migrate and rearrange on the graphene-based surface, which otherwise tend to desorb from the SiO 2 surface given the higher diffusion barrier. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous pinholes were present in STO film (RMS = 1.10 nm), which was in direct contact with Si, whereas a very smooth layer with atomic-scale surface roughness (RMS = 0.34 nm) was observed for STO overgrown on rGO-buffered Si. The lower diffusion energy barrier of rGO compared to that of SiO 2 enables the depositing materials to more easily migrate and rearrange on the graphene-based surface, which otherwise tend to desorb from the SiO 2 surface given the higher diffusion barrier. , …”
Section: Resultsmentioning
confidence: 99%
“…The lower diffusion energy barrier of rGO compared to that of SiO 2 enables the depositing materials to more easily migrate and rearrange on the graphene-based surface, which otherwise tend to desorb from the SiO 2 surface given the higher diffusion barrier. 42,43 After deposition of the STO layer, the light reflected off the sample surface gets reduced compared to bare Si in the ultraviolet, visible, and near-infrared regions (see UV−vis spectra in Figure S5). The improvement of light absorption could be helpful in terms of solar light harvesting as the planar silicon inherently reflects away a certain amount of photons which then cannot be used for the charge carrier generation.…”
Section: Structural and Microstructural Propertiesmentioning
confidence: 99%
“…In recent years, two-dimensional (2D) materials (e.g., graphene and h-BN) have been used as a transition layer on the substrate during III-nitrides epitaxy. The existence of the 2D material between the substrate and the epi-layer can tolerate the mismatch of lattice constants and thermal expansion coefficients. Different from traditional epitaxy, there is only a weak van der Waals force between the substrate and the epi-layer on both sides of the 2D transition layer.…”
Section: Introductionmentioning
confidence: 99%
“…Manufacturing high-quality inorganic thin films on large-area flexible substrates is a key technology required for flexible devices such as wearable sensors, flexible displays, , and electronic devices . One promising approach for the fabrication of flexible devices using inorganic thin films is to grow epitaxial thin films on two-dimensional (2-D) layered materials such as graphene and h -BN since the 2-D materials offer weak bonding with as-grown films for easy exfoliation of epilayers from 2-D materials. , In particular, an epitaxial method called remote epitaxy enables us to grow single-crystalline thin films on graphene-coated polar substrates where the partially screened electrostatic potential of the substrate allows the epitaxial relationship between the substrate and the epilayer. , Recent studies have demonstrated successful remote epitaxy of single-crystalline thin films for various III–V, , III–N, and complex-oxide materials, showing its potential for providing flexible and high-quality material platforms for future device applications. …”
mentioning
confidence: 99%